2010
DOI: 10.1002/jclp.20665
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a Turkish version of the difficulties in emotion regulation scale

Abstract: This study aimed to examine the psychometric properties of the Difficulties in Emotion Regulation Scale (DERS; developed by Gratz & Roemer, 2004) in a Turkish sample. For this purpose, first, the factor structure of the scale was examined with a sample of 338 university students, and an identical factor structure with the original scale was obtained with the exclusion of a single item. Following the confirmation of the 6-factor structure of the scale with the current Turkish sample, the whole scale's and its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
1
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 26 publications
8
75
1
16
Order By: Relevance
“…This finding is overall in line with previous DERS literature ( Giromini et al, 2012;Hervás & Jódar, 2008;Rugancı & Gençöz, 2010), albeit some studies did report statistically significant gender differences for one of the DERS scales, i.e., Awareness (Gratz & Roemer, 2004;Mitsopoulou et al, 2013). In our opinion, because the available studies on the association of gender to DERS scores have so far produced only mixed or controversial results, it is important at this stage of knowledge to retain gender in the equation formulas leading up to the adjusted, normative reference scores for the DERS.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is overall in line with previous DERS literature ( Giromini et al, 2012;Hervás & Jódar, 2008;Rugancı & Gençöz, 2010), albeit some studies did report statistically significant gender differences for one of the DERS scales, i.e., Awareness (Gratz & Roemer, 2004;Mitsopoulou et al, 2013). In our opinion, because the available studies on the association of gender to DERS scores have so far produced only mixed or controversial results, it is important at this stage of knowledge to retain gender in the equation formulas leading up to the adjusted, normative reference scores for the DERS.…”
Section: Discussionsupporting
confidence: 91%
“…Within the Brazilian sample (Miguel et al, 2016), women scored slightly higher than men on Nonacceptance and Impulse, but no other significant gender differences emerged. The Italian (Giromini et al, 2012), Spanish (Hervás & Jódar, 2008, and Turkish (Rugancı & Gençöz, 2010) validation studies of the DERS did not detect any significant gender differences, for any of the DERS scores. Conversely, using a sample of Turkish adolescents, Sarıtaş-Atalar, Gençöz e Özen (2013) recently found that women scored higher than men did on Goals, whereas men scored higher than women did on Awareness; however, no other significant gender differences were observed for any of the other dimensions.…”
Section: Impact Of Gender and Age On Dersmentioning
confidence: 95%
See 1 more Smart Citation
“…Ölçekten alınan yüksek puanlar duygu düzenleme güçlüğüne işaret etmektedir. Ölçeğin Türkçe'ye uyarlanması, geçerlik ve güvenirlik çalışmaları Rugancı ve Gençöz (2010) Romantik Kıskançlık Ölçeği (RKÖ). Pines ve Aronson (1983) tarafından geliştirilen, maddeleri 1-7 arası Likert tipi puanlanan 129 maddelik bir ölçektir.…”
Section: Duygu Düzenleme Güçlüğü öLçeği (Ddgö)unclassified
“…The Cronbach alpha was 0.93 for the overall scale with subscale alphas ranging from 0.80 to 0.98. Rugancı and Gençöz (2010) validated the Turkish version of the DERS and reported a Cronbach's alpha of 0.94 for the overall measure and subscale alphas between 0.75 and 0.90 Symptom Checklist-90. Psychopathological symptoms were measured by the Symptom Checklist-90 (SCL90-R: Derogatis, 1983) which is a 90 item self-report measure.…”
Section: Difficulties In Emotion Regulation Scale (Ders)mentioning
confidence: 99%